2015
DOI: 10.4172/1948-5948.1000230
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Prodigiosin Isolated from Serratia marcescens using Solid State Fermenter and its Bactericidal Activity Compared with Conventional Antibiotics

Abstract: The prodigiosin was isolated from Serratia marcescens and the production process was optimized by response surface methodology-central composite design (CCD). The bactericidal efficiency of prodigiosin was analyzed against antibiotic resistant pathogens. The maximum yield of prodigiosin (70.4023 g) was achieved per kg of tannery fleshing at optimized condition time, 81.2 h; temperature, 29°C; pH, 6.8; moisture, 50%. The prodigiosin exhibited complete inhibition of the growth of Pseudomonas aeruginosa compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…coli , and Klebsiella pneumoniae (Picha et al., 2015). Similar studies reported on the antibacterial activity of Prodigiosin from S. marcescens against P. aeruginosa (Arivizhivendhan et al., 2015) and Prodigiosin from S. marcescens 2170 against some bacterial species.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…coli , and Klebsiella pneumoniae (Picha et al., 2015). Similar studies reported on the antibacterial activity of Prodigiosin from S. marcescens against P. aeruginosa (Arivizhivendhan et al., 2015) and Prodigiosin from S. marcescens 2170 against some bacterial species.…”
Section: Resultssupporting
confidence: 77%
“…The red pigment prodigiosin from S. marcescens PP1 can capable to inhibit the growth of Gram positive bacteria Bacillus sp and S. aureus and gram negative bacteria Pseudomonas aeruginsa, E. coli, and Klebsiella pneumoniae (Picha et al, 2015). Similar studies reported on the antibacterial activity of Prodigiosin from S. marcescens against P. aeruginosa (Arivizhivendhan et al, 2015) and Prodigiosin from S. marcescens 2170 against some bacterial species.…”
Section: Antibacterial Activitysupporting
confidence: 82%
“…with tannery fleshing 1,200 48,000 mg L −1 /40 h 30°C – 8.0 [ 157 ] S. marcescens CF-53 Bioreactor (2 L) Peanut oil cake extract 0.95 40 mg L −1 /42 h 30°C – 7.0 [ 158 ] Serratia sp. KH-95 Bioreactor coupled with extraction system (1 L) 20 g L −1 casein, 1 g L −1 MgSO 4 ⋅7H2O, 1 g L −1 NaCl, and 1.7 g L −1 K 2 HPO 4 400 4,800 mg L −1 /12 h 28°C – 7.0 [ 159 ] S. marcescens JX 1 Bioreactor (200 mL) 20 g L −1 glycerol, 2.0 g L −1 glycine, and 16.0 g L −1 Peptone 135.4 6,500 mg L −1 /48 h 28°C – NR [ 160 ] S. marcescens WT Bioreactor (100 mL) 1% M9 mineral suppl 1% Tannery fleshing 11.9 1,143 mg L −1 /96th 30°C – 6.8 [ 161 ] S. marcescens WT Solid state fermentation (1 Kg) Saline medium supplemented with wheat bran + Tannery fleshing 2,963.7 mg kg −1 h − [ 1 ] 88,910 mg kg −1 /30 days 29°C – 6.8 [ 162 ] S. marcescens UCP 1549 Solid-state fermentation (5 g) Saline medium suppl with food wastes: sugarcane bagasse, instant noodle waste, wheat bran, tangerine peels, pineapple peels, and c...…”
Section: Environmental Factors Influencing Prodigiosin Productionmentioning
confidence: 99%
“…In addition, some biotechnological roles of prodigiosin were already reported to have immunosuppressive, antiproliferative, antimalarial, bactericidal, UV protection, antioxidant, and antitumor properties (Burger and Bennett, 1985; Venil, 2009; Borić et al, 2012; Arivizhivendhan et al, 2015; Darshan and Manonmani, 2015; Lapenda et al, 2015). …”
Section: Introductionmentioning
confidence: 99%